An Exon-Specific U1snRNA Induces a Robust Factor IX Activity in Mice Expressing Multiple Human FIX Splicing Mutants - Dario Balestra; Daniela Scalet; Franco Pagani; Malgorzata Ewa Rogalska; Rosella Mari; Francesco Bernardi; Mirko Pinotti (Elsevier, 2016)
In cellular models we have demonstrated that a unique U1snRNA targeting an intronic region downstream of a defective exon (Exon-specific U1snRNA, ExSpeU1) can rescue multiple exon-skipping mutations, a relevant cause of genetic disease. Here, we explored in mice the ExSpeU1 U1fix9 toward two model Hemophilia B-causing mutations at the 5' (c.519A > G) or 3' (c.392-8T > G) splice sites of F9 exon 5. Hydrodynamic injection of wt-BALB/C mice with plasmids expressing the wt and mutant (hFIX-2G5'ss and hFIX-8G3'ss) splicing-competent human factor IX (hFIX) cassettes resulted in the expression of hFIX transcripts lacking exon 5 in liver, and in low plasma levels of inactive hFIX. Coinjection of U1fix9, but not of U1wt, restored exon inclusion of variants and in the intrinsically weak FIXwt context. This resulted in appreciable circulating hFIX levels (mean ± SD; hFIX-2G5'ss, 1.0 ± 0.5 µg/ml; hFIX-8G3'ss, 1.2 ± 0.3 µg/ml; and hFIXwt, 1.9 ± 0.6 µg/ml), leading to a striking shortening (from ≃100 seconds of untreated mice to ≃80 seconds) of FIX-dependent coagulation times, indicating a hFIX with normal specific activity. This is the first proof-of-concept in vivo that a unique ExSpeU1 can efficiently rescue gene expression impaired by distinct exon-skipping variants, which extends the applicability of ExSpeU1s to panels of mutations and thus cohort of patients.